2020
DOI: 10.3389/fpsyg.2020.566108
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Willingness to Share COVID-19 Misinformation

Abstract: We conducted a preregistered exploratory survey to assess whether patterns of individual differences in political orientation, social dominance orientation (SDO), traditionalism, conspiracy ideation, or attitudes about science predict willingness to share different kinds of misinformation regarding the COVID-19 pandemic online. Analyses revealed two orthogonal models of individual differences predicting the willingness to share misinformation over social media platforms. Both models suggest a sizable role of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 29 publications
1
59
1
1
Order By: Relevance
“…To our knowledge, until recently, there is only one study on COVID-19 conspiracy theories that included measures of both authoritarianism and social dominance. Results indicated that both variables were positively correlated with belief in COVID-19 conspiracy theories (Lobato et al, 2020). Abalakina-Paap et al (1999) proposed five types of reasons of why people believe in conspiracy theories: alienation, powerlessness, simplification of the complex world, explanation of their problems, and providing an opportunity for their hostility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, until recently, there is only one study on COVID-19 conspiracy theories that included measures of both authoritarianism and social dominance. Results indicated that both variables were positively correlated with belief in COVID-19 conspiracy theories (Lobato et al, 2020). Abalakina-Paap et al (1999) proposed five types of reasons of why people believe in conspiracy theories: alienation, powerlessness, simplification of the complex world, explanation of their problems, and providing an opportunity for their hostility.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, only a few studies examined general trust in science and scientists as a predictor of acceptance of conspiracy theories. In the context of belief in COVID-19 conspiracy theories, research showed that science skepticism was strongly associated with endorsement and willingness to spread COVID-19 conspiracies (Lobato et al, 2020) and that trust in scientists was negatively related to believing in COVID-19 conspiracies (Constantinou et al, 2020). Furthermore, trust in science had a mediating role in the relationship between conspiracy ideation and willingness to accept prevention guidelines (Plohl and Musil, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, older, politically conservative individuals have been found to be more willing to share misinformation than their younger more liberal counterparts [ 17 ]. Similarly, aspects of political belief including social dominance orientation, has been found to predict the sharing of misinformation [ 18 ]. It was thus of interest in the present study to determine whether predictors of the inclination to share misinformation (or possible misinformation) in our sample are comparable to predictors in general samples.…”
Section: Introductionmentioning
confidence: 99%
“…This information requires in-depth understanding, context, or additional explanations to avoid inappropriate conclusions 103 . In a published report, 48% of 8914 Americans surveyed stated that they heard "at least some [COVID- 19-related] made-up news and information" 104 . There are countless examples of false information that has spread across the United States, and there is no one person who is immune to either receiving this information and/or spreading it.…”
Section: Navigating the Infodemic Eramentioning
confidence: 99%